Complementary medicines use amongst elective surgery patients at a public tertiary hospital: A prospective observational cohort study in Australia. (May 2019) - Guilmetdinov, Edouard Faridovich; Al-Khalaf, Marwah; Bhatt, Jilna; Parsons, Richard; Sim, Tin Fei
Abstract: Background: and purpose. Complementary medicines (CM) use may result in untoward effects perioperatively. The study purpose is to identify CM pattern of use amongst elective surgery patients, and improve effectiveness of information collection relating to CM use. Materials and methods: This is a prospective observational cohort study. CM questionnaire was administered alongside standard hospital forms at pre-admission clinic over eight weeks. Results: 992 patients attended pre-admission clinic; 317 patients were included in analysis. Introduction of CM questionnaire increased disclosure rate by 11.7% giving a total prevalence of 44.2%. CM use was significantly higher in females and in older patients. Top CM reported were vitamin D (12%) and omega-3 (12%). Majority of patients did not plan to withhold CM before surgery, and were not concerned about perioperative risks. Conclusion: Pre-admission clinics need to encourage CM disclosure. Patient education of potential risks and greater engagement of clinicians in patient assessment is required. Highlights: Intervention to encourage disclosure of CM increased patient disclosure rate by 11.7%, giving a total CM prevalence of 44.2%. Females and older patients were more likely to use CM, with the most commonly used CM being vitamin D and omega-3. There is a lack of understanding about CM safety amongst patients which places them at risk of perioperative complications. Patient education of potential risks and greater engagement of clinicians in patient assessment is warranted.